Spatial and temporal genetic structure of Symbiodinium populations within a common reef‐building coral on the Great Barrier Reef. Issue 14 (4th June 2013) - Howells, Emily J.; Willis, Bette L.; Bay, Line K.; van, Madeleine J. H.
Abstract The dinoflagellate photosymbiont Symbiodinium plays a fundamental role in defining the physiological tolerances of coral holobionts, but little is known about the dynamics of these endosymbiotic populations on coral reefs. Sparse data indicate that Symbiodinium populations show limited spatial connectivity; however, no studies have investigated temporal dynamics for in hospite Symbiodinium populations following significant mortality and recruitment events in coral populations. We investigated the combined influences of spatial isolation and disturbance on the population dynamics of the generalist Symbiodinium type C2 (ITS1 rDNA) hosted by the scleractinian coral Acropora millepora in the central Great Barrier Reef. Using eight microsatellite markers, we genotyped Symbiodinium in a total of 401 coral colonies, which were sampled from seven sites across a 12‐year period including during flood plume–induced coral bleaching. Genetic differentiation of Symbiodinium was greatest within sites, explaining 70–86% of the total genetic variation. An additional 9–27% of variation was explained by significant differentiation of populations among sites separated by 0.4–13 km, which is consistent with low levels of dispersal via water movement and historical disturbance regimes. Sampling year accounted for 6–7% of total genetic variation and was related to significant coral mortality following severe bleaching in 1998 and a cyclone in 2006. Only 3% of the total genetic variation was related to coral bleaching status, reflecting generally small (8%) reductions in allelic diversity within bleached corals. This reduction probably reflected a loss of genotypes in hospite during bleaching, although no site‐wide changes in genetic diversity were observed. Combined, our results indicate the importance of disturbance regimes acting together with limited oceanographic transport to determine the genetic composition of Symbiodinium types within reefs.